Direct and Indirect Effects of Housing Market Policies using an Augmented DiPasquale-Wheaton framework - Trond-Arne Borgersen; Anne Wenche Emblem (Tidsskrift for boligforskning)
This paper analyses a set of housing market policies in an augmented DiPasquale-Wheaton (ADPW) model where the price-rent (PR) ratio ensures housing market equilibrium across different types of tenure. The aim of the paper is educational, putting several housing market policies into a comprehensive context where the rental housing market, the housing construction industry and the market for owner-occupied housing are interrelated. Housing market dynamics takes both direct and indirect effects into account. The paper finds that introducing tax-deductible mortgage interest rates has a positive effect on house prices. This policy stimulates housing starts and pushes down rental prices. A property tax has a negative effect on house prices while lifting the rental price as the housing industry contracts. Social housing policy interventions on the supply side of the housing market partly crowd out commercial housing supply. Demand-side vouchers have stronger short-run effects as long-run effects incorporate the housing construction industry’s reaction to house price signals. Finally, rental subsidies create a gap between the rent paid by a tenant and the rent received by a landlord. The aggregate effect of a rental subsidy is related to the elasticities of supply and demand, where not only renters, but also homeowners and landlords, may benefit when supply and demand are very elastic.